The genome of newly classified Ochroconis mirabilis: Insights into fungal adaptation to different living conditions - Yew, S.M.; Chan, C.L.; Kuan, C.S.; Toh, Y.F.; Ngeow, Y.F.; Na, S.L.; Lee, K.W.; Hoh, C.C.; Yee, W.Y.; Ng, K.P. (BioMed Central, 2016)
Background: Ochroconis mirabilis, a recently introduced water-borne dematiaceous fungus, is occasionally isolated from human skin lesions and nails. We identified an isolate of O. mirabilis from a skin scraping with morphological and molecular studies. Its genome was then sequenced and analysed for genetic features related to classification and biological characteristics. Results: UM 578 was identified as O. mirabilis based on morphology and internal transcribed spacer (ITS)-based phylogeny. The 34.61Mb assembled genome with 13,435 predicted genes showed less efficiency of this isolate in plant cell wall degradation. Results from the peptidase comparison analysis with reported keratin-degrading peptidases from dermatophytes suggest that UM 578 is very unlikely to be utilising these peptidases to survive in the host. Nevertheless, we have identified peptidases from M10A, M12A and S33 families that may allow UM 578 to invade its host via extracellular matrix and collagen degradation. Furthermore, the lipases in UM 578 may have a role in supporting the fungus in host invasion. This fungus has the potential ability to synthesise melanin via the 1,8-dihydroxynaphthalene (DHN)-melanin pathway and to produce mycotoxins. The mating ability of this fungus was also inspected in this study and a mating type gene containing alpha domain was identified. This fungus is likely to produce taurine that is required in osmoregulation. The expanded gene family encoding the taurine catabolism dioxygenase TauD/TdfA domain suggests the utilisation of taurine under sulfate starvation. The expanded glutathione-S-transferase domains and RTA1-like protein families indicate the selection of genes in UM 578 towards adaptation in hostile environments. Conclusions: The genomic analysis of O. mirabilis UM 578 provides a better understanding of fungal survival tactics in different habitats.